An Invisible School: Social-Cultural Work of the Mosque Organizations - Yar, Hasan (Religions, 2023)
There is a knowledge gap in the contribution of socio-cultural work in Islamic organisations to the participants’ learning and development. This article focuses on the role of the socio-cultural work of Islamic organizations as a form of non-formal education. Education is the internal process of a person which leads to a better understanding of themself and their situation, a critical appreciation of their situation and a conscious and targeted use of the possibilities in their social situation. Therefore, what volunteers learn when they participate in socio-cultural work in mosque organizations will be investigated. The research is based on the case study of a Turkish faith-based organization Milli Görüş Amsterdam-West (MGAW) and its volunteers. The method of the research is ethnographic field research. The research focuses on a specific group of participants, namely, the volunteers who are active at the MGAW. One of the results of the research is that the participants who follow the social-cultural activities of MGAW for a certain period develop a cohesive worldview whereby volunteering becomes a virtue.